Synthesis a Novel Complexes of VO(II),Mn(II),Fe(II) ,Co(II), Ni(II), Cu(II)and Pt(IV) Derived from Schiff’s Base of Pyridoxal and 2-amino-4-nitrophenol and Study their Biological Activates - Ahmed A. Ismail,; M. Lateef , Sajid (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
This work describes the synthesis of novel ligand (H2L2) (4-((2-hydroxy-5-nitrophenyl)imino)methyl)-5(hydroxymethyl)-2methylpyridin-3-ol)  type (NOO) donor atoms. When it coordinates with metal ions[V2+,Mn2+,Fe2+,Co2+,Ni2+,Cu2+and Pt4+] with the general formula K2[M(L2)2].XH2O and K2[VO(L2)(OSO3)].H2O . This ligand can form tridentate structures. The ligand was synthesized from the reaction of pyridoxal hydrochloride with 2-amino-4-nitrophenol in ethanol (as a solvent) at a mole ratio of 1:1 and thoroughly mixed and refluxed for 6-8  hrs . The reaction was monitored using TLC (Ethylactate/hexane 1:1). The structures of the ligand and the complexes were characterised using spectroscopic techniques such as (FT-IR, 1HNMR, 13CNMR, UV-Vis, and Mass spectroscopy). In addition, molar conductance, magnetic susceptibility, elemental analysis, and thermo gravimetric, melting points were also measured for complexes. The antibacterial activities of the obtained products were tested against G- bacteria (Klebsiella pneumoniae and pseudomonas), G+ bacteria (Staphylococcus aureus and Bacillus subtilis). In addition, antifungal action was tested against (Candida albicans). The results were good in both tests.